THE INFLUENCE OF FINANCING TO DEPOSIT RATIO (FDR), NON PERFORMING FINANCING (NPF) AND BOPO ON ZAKAT COMPLIANCE IN ISLAMIC BANKS IN INDONESIA PERIOD 2011-2015 - Tri Utami (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
This study aimed to examine the influence of financial performance that is Financing to Deposit Ratio (FDR), Non Performing Financing (NPF) and Operating Expenses to Operating Income (BOPO) of the Compliance Zakat in Islamic Banks in Indonesia. The data used in this study was obtained from the data Condensed Financial Statements Annual Islamic Banks 2011-2015 period The population in this study were 12 Islamic Banks in Indonesia. To determine the author of a sample using the purposive sampling method, obtained 10 Islamic Banks are suitable for use in further research. The analysis technique used in the study is binary logisticregression that aims to obtain a comprehensive picture of the relationship between variables. In conducting a test of hypothesis, first tested the feasibility of a regression model (goodness of fit), the overall assessment models (overall model fit) and the accuracy of regression (classification table). The results showed that the variables simultaneously FDR, NPF and BOPO have significant influence on Compliance Zakat 0,000 <0,05, while partial variable FDR significant negative effect on Compliance Zakat Islamic Banks. while the NPF variables and BOPO has a negative effect and no significant effect on Compliance Zakat. The predictive ability of the three variables by 80%, rest influenced by other factors outside theresearch model. The results of this study are expected to be a guideline for the management of Islamic Banks in managing the company, so as to increase awareness of Islamic Banks in paying zakat in accordance with the provisions of sharia. for regulators and governments can add the Act relating to obligations and terms of payment of zakat enterprises and for further research to be able to add more independent variables.